2017
DOI: 10.1073/pnas.1620194114
|View full text |Cite
|
Sign up to set email alerts
|

Nasal-associated lymphoid tissues (NALTs) support the recall but not priming of influenza virus-specific cytotoxic T cells

Abstract: The lymphoid tissue that drains the upper respiratory tract represents an important induction site for cytotoxic T lymphocyte (CTL) immunity to airborne pathogens and intranasal vaccines. Here, we investigated the role of the nasal-associated lymphoid tissues (NALTs), which are mucosal-associated lymphoid organs embedded in the submucosa of the nasal passage, in the initial priming and recall expansion of CD8+ T cells following an upper respiratory tract infection with a pathogenic influenza virus and immuniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…Studies in guinea pigs also demonstrated that priming with the 2009 pandemic H1N1 virus confers protection against the 2013 avian H7N9 IAV [62]. Recently influenzaspecific tissue-resident memory (TRM) CD8 + T cells in the upper respiratory tract of mice were shown to be important in mediating protection from pulmonary influenza virus infection [63].…”
Section: Cd8 + T Cells Confer Cross-protection Across Different Influmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in guinea pigs also demonstrated that priming with the 2009 pandemic H1N1 virus confers protection against the 2013 avian H7N9 IAV [62]. Recently influenzaspecific tissue-resident memory (TRM) CD8 + T cells in the upper respiratory tract of mice were shown to be important in mediating protection from pulmonary influenza virus infection [63].…”
Section: Cd8 + T Cells Confer Cross-protection Across Different Influmentioning
confidence: 99%
“…The presence of protective CD8 + TRM populations in the nasal tissue implies that these cytotoxic effectors are in place to contribute to the early control of infection. Indeed, in mouse studies the establishment of CD8 + TRM cells in the upper respiratory tract reduced viral replication in the nose as early as day 3 and day 5 after intranasal challenge, in a CD8 + T celldependent manner [63].…”
Section: Cd8 + T Cells Confer Cross-protection Across Different Influmentioning
confidence: 99%
“…73,85,86 Virus-specific CD69 + and CD69 + CD103 + CD8 + T cells carrying common T RM signature genes can be readily isolated from upper respiratory tract including nasal tissue and nasal-associated lymphoid tissues in mouse and tonsils in human. Distinct from TGF-β- and cognate antigen-dependent induction of lung T RM cells, both TGF-β and cognate antigen recognition are dispensable for upper respiratory tract T RM cells.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…The CXCR3 family chemokine CXCL10 is an IFNα/β signature gene, upregulated in patients with SLE . The CXCR3 chemokines CXCL9 and CXCL10 promote cell recruitment to sites of inflammation . During viral infection, DC‐derived CXCL10‐CXCR3 interactions can optimize both T‐ and B‐cell responses .…”
Section: Introductionmentioning
confidence: 99%